Expressed Emotion and Attributions in Relatives of Patients With Obsessive-Compulsive Disorder and Panic Disorder. Issue 4 (April 2017) - Renshaw, Keith D.; Chambless, Dianne L.; Thorgusen, Sommer
Abstract : Abstract: Relatives' criticism of, hostility toward, and emotional overinvolvement (EOI) with patients are predictive of treatment response and relapse. Although these constructs have been linked to relatives' attributions for patient problems, little research has yet evaluated attributions for specific types of problems. This study examined event-specific attributions ( i.e., attributions specifically for either disorder-related [DR] or non-DR problems) in relatives of patients with anxiety disorders. Relatives made more illness attributions (attributing problems to a patient's disorder) than controllable attributions (attributing problems to factors controllable by patients) for DR events, with the reverse pattern for non-DR events. Criticism and hostility were associated primarily with controllability attributions for non-DR events. In contrast, the presence of EOI was associated with illness attributions for non-DR events. Family-based interventions for anxiety disorders might need to focus on relatives' controllability attributions for a broad range of patient behaviors and on reducing tendencies to attribute non-DR problems to patients' disorders.